PENGGUNAAN MEDIA PUZZLE MELALUI BIMBINGAN KELOMPOK UNTUK MENGATASI KEJENUHAN BELAJAR SISWA DI SMP NEGERI 1 BAITUSSALAM - Andini Nur Hanani; Wanty Khaira (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of using crossword puzzle media through group guidance services in overcoming learning burnout among students at SMP Negeri 1 Baitussalam. The research utilizes a quantitative approach with a one-group pretest–posttest experimental design. The research subjects consisted of 6 students who had high levels of learning burnout based on pretest results. The media used in this study is a crossword puzzle developed by the researcher and has undergone a judgment process by media experts. The research instrument is a learning burnout questionnaire that has been tested for validity and reliability. Data collection was carried out through a pretest, the implementation of treatment across three sessions using puzzle media within group guidance services, and a posttest. Data analysis utilized the Shapiro–Wilk normality test and the Paired Sample t-test hypothesis test with the assistance of SPSS version 26. The results showed a decrease in students' learning burnout levels after the treatment, with a significance value (Sig. 2-tailed) of 0.000 < 0.05. Thus, the use of crossword puzzle media through group guidance services is effective in overcoming student learning burnout